International Child Health Group 2018
DOI: 10.1136/archdischild-2018-rcpch.268
|View full text |Cite
|
Sign up to set email alerts
|

G276(P) Neonatal mortality in western uganda

Abstract: AimsNeonatal mortality in Uganda has not improved in the last 14 years and remains between 24 and 27 deaths per 1000 live born infants, which compares poorly to the UK neonatal mortality (2.4 per 1000 live born infants). Our aim was to determine the immediate and long-term impact of introduction of low-cost guidelines on neonatal mortality in a low-income setting.MethodsNeonatal mortality was audited for three months prior to the intervention. The intervention consisted of guidelines developed using a literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…On a smaller scale Harris et al reported results from a pre- post-implementation trial aiming to improving neonatal outcomes in a single Ugandan neonatal unit [ 198 ]. Protocols for management of unwell newborns were developed using literature and local consensus and disseminated through ward meetings and regular ward-based teaching.…”
Section: Resultsmentioning
confidence: 99%
“…On a smaller scale Harris et al reported results from a pre- post-implementation trial aiming to improving neonatal outcomes in a single Ugandan neonatal unit [ 198 ]. Protocols for management of unwell newborns were developed using literature and local consensus and disseminated through ward meetings and regular ward-based teaching.…”
Section: Resultsmentioning
confidence: 99%